2011
DOI: 10.19030/jbcs.v4i7.4794
|View full text |Cite
|
Sign up to set email alerts
|

The Film Philadelphia As A Case Study Of Ethical Dilemmas In The Workplace

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Many other studies in social sciences (such as history, English, psychology, business, and etc.) have empirically showed that; films are effective tools to increase students' interest, understanding and engagement in the courses (Foreman & Thatchenkery, 1996;Scherer & Baker, 1999;Champoux, 1999;Comer, 2001 ;Champoux, 2004;Clawson, 2006;Frieden & Deborah, 2007;Gonzales & Zarzosa, 2008;Butler, et.al., 2009). Using films as an educational resource to illustrate business management concepts like ethical decision-making, risk taking, leadership, communication, strategic management and, organizational culture have also been discussed by many researchers (Scherer & Baker, 1999;Champoux, 1999;Mallinger & Rossy, 2003;Champoux, 2006;Ambrosini, Billsberry and Collier, 2008;Butler, et.al, 2009;Tyler, Anderson and Tyler, 2009;Smith, 2009).…”
Section: Teaching With Filmsmentioning
confidence: 99%
“…Many other studies in social sciences (such as history, English, psychology, business, and etc.) have empirically showed that; films are effective tools to increase students' interest, understanding and engagement in the courses (Foreman & Thatchenkery, 1996;Scherer & Baker, 1999;Champoux, 1999;Comer, 2001 ;Champoux, 2004;Clawson, 2006;Frieden & Deborah, 2007;Gonzales & Zarzosa, 2008;Butler, et.al., 2009). Using films as an educational resource to illustrate business management concepts like ethical decision-making, risk taking, leadership, communication, strategic management and, organizational culture have also been discussed by many researchers (Scherer & Baker, 1999;Champoux, 1999;Mallinger & Rossy, 2003;Champoux, 2006;Ambrosini, Billsberry and Collier, 2008;Butler, et.al, 2009;Tyler, Anderson and Tyler, 2009;Smith, 2009).…”
Section: Teaching With Filmsmentioning
confidence: 99%